Perbandingan Kandungan Fenolik Total Dan Antioksidan Ekstrak Akar Tapak Liman (Elephantopus scaber Linn Dan Elephantopus mollis Kunth) - Mega Yulia; Adelya, Melta; Nurdin, Hazli; Fera, Okta (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2026)
Two species of tapak liman plants commonly known in Indonesia, Elephantopus scaber Linn and Elephantopus mollis Kunth, belonging to the Asteraceae family, are known to have many health benefits. Tapak liman plants produce secondary metabolites such as phenolics. Phenolic compounds are known to act as antioxidants. This study aims to determine the comparison of total phenolic content in ethanol extracts of E. scaber and E. mollis roots, as well as the comparison of antioxidant activity between E. scaber and E. mollis roots using the DPPH method. The results of phytochemical screening of ethanol extracts from E. scaber and E. mollis roots revealed the presence of phenolic compounds, flavonoids, and terpenoids. The total phenolic compound content in E. scaber samples was determined to be 4.31% and in E. mollis samples to be 2.35%. The determination of the maximum absorption wavelength of DPPH at 35 µg/ml using a UV-Vis spectrophotometer showed a maximum absorption wavelength of 519 nm with an absorbance of 0.610. The antioxidant activity of the ethanol extract of E. scaber roots was obtained with an IC50 of 131.4431 µg/ml, while that of E. mollis roots was 106.4321 µg/ml. Based on these results, it can be concluded that the total phenolic content of the ethanol extract of E. scaber roots is higher than that of E. mollis roots. Furthermore, the antioxidant activity of the E. scaber root extract is stronger than that of the E. mollis root extract, but both still fall into the same category, namely the moderate category. Based on statistical tests using the T test, it shows that the significant differences for phenolic content and not significant for antioxidant activity (p < 0.05).